Prototipe Alat Ukur Detak Jantung Menggunakan Sensor MAX30102 Berbasis Internet of Things (IoT) ESP8266 dan Blynk - Muthmainnah Muthmainnah; Deni Bako Tabriawan (UIN Sunan Kalijaga Yogyakarta, 2022)
The heart is an important organ of the human body. The heart functions to pump blood throughout the body. Health conditions can be seen in the condition of heart function. The heart’s function can be known through the beat when pumping blood. The manufacture of a heart rate device has been carried out using the PPG method. This tool uses the MAX30102 sensor as input. The measurement results are displayed on the smartphone. This tool can calculate the heart rate by sticking the surface of the fingertips for ten seconds. The light waves emitted by the sensor source will hit the surface of the finger. Changes in blood volume cause changes in light intensity according to what is received by the sensor. Based on the test results, the average standard deviation of this tool's heart rate measurement is 1.176. If considered the data from the pulse oximeter is correct, then this tool has an accuracy of 98.804%.